Is there any association between colonic polyps and gastric intestinal metaplasia? - Kanat Ünler, Gülhan; Teke Özgür, Gülsüm; Göktürk, Hüseyin Savaş; Korkmaz, Hüseyin; Erinanç, Özgür Hilal (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Chronic gastritis progression is a multistep process of atrophy, intestinal metaplasia (IM), and dysplasia, which may lead to invasive carcinoma. In this study, we identified an association of colonic polyps with gastric IM in patients undergoing colonoscopy. Materials and Methods: This retrospective case-control, cross-sectional study was conducted in a tertiary-care institution in Turkey. Pathology and endoscopy reports were reviewed. The study group comprised 400 patients with colonic adenomatous polyps, and the control group comprised 360 patients without colonic adenomatous polyps on colonoscopy. Results: The risk of gastric IM was 1.42-fold higher in the study group (p<0.05). The risk of IM in patients aged ≥50 years with colonic polyps was 3.35-fold higher than in those aged <50 years (p<0.05). The risk of Helicobacter pylori infection in the study group was 1.07-folder higher than that in the control group (p<0.05). H. pylori infection prevalence was higher only in patients with high-grade colonic polyp dysplasia (p<0.05). There were no statistically significant differences in the proportion of incomplete IM between the groups (p<0.05). Conclusion: This study observed increased rates of gastric IM with colonic polyps. An increased risk of gastric IM was associated with higher grades of polyp dysplasia.